Oral Nitrate Reductase Activity Is Not Associated with Development of Non-Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH): A Pilot Study - Barzin, Gilda (Iranian Association of Gastroerterology and Hepatology, 2014)
BACKGROUND NAFLD/NASH is a manifestation of metabolic syndrome and is associated with obesity/overweight. Not all obese/overweight individuals develop NASH. Gastro-esophageal reflux disease (GERD) is considered a gastrointestinal manifestation of the metabolic syndrome and is associated with obesity/overweight. Again not all obese/overweight individuals develop GERD. Recent data show association of dietary nitrate content and oral nitrate reductase activity (NRA) with GERD. Nitrates need to be converted to nitrite (done in human beings by nitrate reductase of oral bacteria exclusively) to be active in metabolic pathways. OBJECTIVE To assess the relation between NASH/NAFLD and oral NRA. METHODS Oral NRA was measured in individuals with NASH (compatible abdominal ultrasound and two elevated ALT/AST levels over six months) and was compared with that of those without NASH. Oral NRA was measured according to a previously reported protocol. RESULTS Eleven NASH patients and twelve controls were enrolled. Mean oral NRA activity were 2.82 vs. 3.51 μg nitrite-N formed per person per minute for cases and controls respectively (p=0.46). CONCLUSION According to our data, oral nitrite production is not different between individual swith and without NASH.